Luther and the beloved community: a path for Christian theology after Christendom - Hinlicky, Paul R. (Eerdmans, 2010)
Part I. Luther's Creedal Theology : -- 1. The problem of Christian belief in Euro-America today -- 2. "One of the Trinity suffered": Luther's neo-Chalcedonian Christology -- 3. God surpassing God by "Christ made to be sin" -- 4. Trinitarian advent: resituating the dialectic of law and gospel -- Part II. Explorations in theological anthropology : -- 5. Somatic self, ecstatic self: Luther on theonomy -- 6. The redemption of the body: Luther on marriage -- Part III. Some objections regarding Justification, the Church, and political theology : -- 7. "New, old, and different perspectives" on Paul (Augustine and Luther) -- 8. Communio: Luther's forgotten ecclesiology -- 9. Passion and action in Christ: political theology between the times -- 10. By way of conclusion: what Luther meant by "theologia crucis" -- Appendix: the problem of demonization in Luther's apocalyptic theology